PENGARUH PERLAKUAN KONSENTRASI AIR KELAPA MUDA TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS TANAMAN KANGKUNG DARAT (Ipomea reptans P.) - Kartina Kartina; Nuniek Herminta; Sutrisna Sutrisna (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2022)
This research was aimed to know the effect of concentration treatment young coconut water on the growth and result of three Varieties Land Water Spinach. This research was conducted from May until June 2021 at Cikupa, Tangerang. This Research used Randomized Completely Block Design (RCBD), consisted two factors. The first factor was concentration of young coconut water with four level, namely: K0 = control without concentration young coconut water, K1 = 225 ml concentration of young coconut water, K2 = 250 ml concentration of young coconut water, and K3 = 275 ml concentration of young coconut water. The second factor was Varieties of land water spinach with three level, namely: V1= Bangkok, V2= Bisi, V3=Bika. Each treatments repeated 3 times. Parameters observed were plant height, number of leaves, fresh weight per plant, and root long. The result showed that, 275 ml concentration of young coconut water gave the best result on the parameter plant height in 7 Day After Planting (DAP): 9,69 cm; 14 DAP (19,99 cm); 21 DAP (33,20 cm); and 28 DAP (47,03). The treatment of three Varieties, Bangkok gave the best result on number of leaves in 7 DAP (2,00 sheets). There were interaction between the treatment of concentration young coconut water and Varieties of land water spinach on the parameter plant height (28 DAP) and number of leaves (7 DAP). Key Words: Young Coconut Water, Varieties of land water Spinach